Scaling up research on family justice using large-scale administrative data: an invitation to the socio-legal community. Issue 3 (3rd July 2021) - Broadhurst, Karen; Cusworth, Linda; Harwin, Judith; Alrouh, Bachar; Bedston, Stuart; Trinder, Liz; Jones, Kerina; Ford, David; Griffiths, Lucy
ABSTRACT: This article outlines the value of administrative data for family justice research. Although socio-legal scholars have extended their research beyond purely theoretical or doctrinal analyses, studies using large-scale digital datasets remain few in number. As new opportunities arise to link large-scale administrative datasets across health, education, welfare and justice, it is vital that the community of family justice researchers and analysts are supported to deliver research based on entire service or family court populations. In this context, this article provides a definition of administrative data, before outlining the potential of single, linked or blended administrative data sets for family justice research. The remaining sections of the article speak to questions that are pertinent to this particular academic community, including the distinctive contribution of the socio-legal scholar to interdisciplinary teams and the place of data providers in collaborative research. Drawing on the sociological concept of 'publics', the final section considers the multiple interest groups whose social licence must be secured, when personal records are used to understand the relationship between law and family life.